LaNPro: Non Stop Driving Thru Low Traffic Intersections - Silva, Cristiano; Aquino, Andre; Meira Jr., Wagner (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2014)
LaNPro is a vehicular client-server application that avoids the stop of vehicles at traffic lights in low traffic conditions. The server-side of the application is deployed as a module of a smart traffic light. It senses the presence of vehicles along the road through radars, cameras, road sensors and Wi-Fi communication to assign the right of way. The client-side of the application runs inside the vehicle’s on-board unit. Results (via simulation) show that the application can ensure the non-stop drive thru of intersections that have an expected traffic volume equal or less than λ = 0.10 vehicles per second, assuming intersections of 2, 3 and 4 lanes. This works presents strategies to deal with the allocation of vehicles in low traffic intersections and presents the scenario where this technique can be used.